Trusts and Foundations: Implications of Common Reporting Standard and Anti-money Laundering Legislation. Issue 6 (28th June 2018) - Russell, David
Abstract: To the already onerous duties of trustees and councillors of foundations we can now add to the obligations that flow from the enactment at national level of the recommendations of the Financial Action Task Force, supplemented in the European Union anti-money laundering directives, and the laws designed to give effect to the common reporting standard. Non-compliance with these laws brings with it substantial penalties. However, inaccurate characterization of the status of individuals who are the subject of reports under them can also lead to significant risks for the people concerned, and place a trustee in breach of the trustee's fiduciary duties, given that the obligations of trustees do not extend to subjecting beneficiaries and others to investigations and tax assessments where these are not justified by law. Another thing that needs to be noted is the somewhat different application of the reporting regime in relation to trusts on the one hand and foundations on the other. The present article examines the UK legislation as an example and points out uncertainties and deficiencies in its reporting regime.